Thinking about Latin American integration: also from the organizational communication and public relations standpoint - Suárez Monsalve, Ana María (Organicom, 2011)
This article discusses the need to consider the organizational communicator and public relations as an actor in the integration process of Latin American society from the regional to global. This idea is present in the powers of communication in Latin America, but most of the analysis will focuse on media, journalism or public communication. It has been ignored the potential for this purpose, action and orientation of the communities and relationships in organizations, public and private, as an actor in the construction work of Latin American integration.